Assessment of the transforming impact of global value chains on international trade - Smirnov E.N. (Ural State University of Economics, 2019)
The article discusses the problems of international fragmentation of production and global value chains and how they relate to modern aspects, trends and challenges of international trade development. Methodologically the research rests upon the key principles of classical and alternative theories of international trade, the theory of value chains and the basic theories of foreign investment. In the course of the study, the authors apply both general theoretical (formalization, synthesis, analysis) and particular (measurement, comparison, observation) research methods. The main results of the research are as follows: a conceptual rethink of the nature of today’s international trade in terms of influencing factors of global production decomposition; theoretical justification and criticism of contemporary approaches to the organization of value chains between developed and developing countries; the formulation of measures to modify trade and economic policy in the current system-related and structural challenges of value chains’ transformation. The authors conclude that instability of modern global value chains in the world production and international trade is due to the unsteady dynamics of the global economy, industrial differentiation of global value chains, changes in international strategies of multinational companies, innovation and digitalization of global production networks.